2015
DOI: 10.1155/2015/381275
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Multiwall Carbon Nanotubes in Organic Solvents through Hydrothermal Supercritical Condition

Abstract: Multiwall carbon nanotube (MWCNT) composite materials require careful formulation of processing methods to ultimately realize the desired properties. Until now, controlled dispersion of MWCNT remains a challenge, due to strong van der Waals binding energies associated with the MWCNT aggregates. In the present study, an effort has been made to disperse MWCNTs in organic solvents like dichloromethane, ethanol, isopropyl alcohol, and hexane through hydrothermal reaction. Dichloromethane is considered the best sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
1
8
0
2
Order By: Relevance
“…Two CNT/[bisC 8 ImC 10 ][C 12 H 25 OSO 3 ] 2 mixtures with different amounts of CNTs (0.5% w/w and 0.05% w/w) were prepared for dielectric measurements by consecutive dilution of an initial sample containing 2% CNTs. The starting sample was prepared by dissolving first the bisimidazolium salt (0.2 g) in a minimum volume of dichloromethane (1 mL) followed by addition of CNT (0.004 g) [ 58 ]. The resulting mixture was sonicated for at least 60 min followed by the removal of the solvent, drying in vacuum and cooling at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Two CNT/[bisC 8 ImC 10 ][C 12 H 25 OSO 3 ] 2 mixtures with different amounts of CNTs (0.5% w/w and 0.05% w/w) were prepared for dielectric measurements by consecutive dilution of an initial sample containing 2% CNTs. The starting sample was prepared by dissolving first the bisimidazolium salt (0.2 g) in a minimum volume of dichloromethane (1 mL) followed by addition of CNT (0.004 g) [ 58 ]. The resulting mixture was sonicated for at least 60 min followed by the removal of the solvent, drying in vacuum and cooling at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…PZT was used as a model high-dielectric ceramic filler and its content was fixed at 0-5-10-20-30 vol% and MWCNT was employed as the conductive filler with 0-1 vol% content. Dispersion of MWCNTs is a challenging assignment, due to their high aspect ratio and strong van der Waals bonds [54]. Poor dispersion results in bundles of entangled MWCNT.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the filtrate was dried in an oven (Figure S1b) and sonicated for 5 min with 60 mL of DI water to make the F-MWCNT solution. As shown in Figure S1c, our F-MWCNTs were uniformly dispersed in DI water because they have better dispersion than MWCNTs in water [34]. The FTIR spectra (Figure 1), showed that there were O-H, C=O, and C-O vibrations at 3372.11, 1642.21, and 1226.28 cm −1 , respectively, which clearly indicated that carboxylic and hydroxyl groups had been successfully attached to the surface of the MWCNTs.…”
Section: Procedures 231 Preparation Of Functionalized Cntsmentioning
confidence: 83%